(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The aim of this paper is to analyze the foreign policy activism of former Republican Congressman Dan Burton during the 1992–1995 war in Bosnia. Based on Burton’s newly accessible congressional papers, this article traces the Indiana Republican’s efforts to influence US policy towards Bosnia. Opposed to any US involvement in Bosnia, Burton’s views reflected the Serbian-American diaspora’s policy positions on Bosnia. Though ultimately unsuccessful, Burton’s efforts in the early 1990s provide a glimpse into how opponents of American intervention in Bosnia operated.